Cross‐Linked Protein Crystals With an Intense Nonconventional Full‐Color Photoluminescence Originating From Through‐Space Intermolecular Interaction - Renbin Zhou; Xiaoli Lu; Xuefeng Zhou; Xuejiao Liu; Shanmin Wang; Tymish Y. Ohulchanskyy; Da‐Chuan Yin; Junle Qu (Aggregate)
ABSTRACT The emergence of nonconventional luminescent materials (NLMs) has attracted significant attention due to their sustainable synthesis and tunable optical properties. Yet, establishing a clear structure–emission relationship remains a challenge. In this work, we report a previously unknown class of NLMs: cross‐linked protein crystals that exhibit intense photoluminescence (PL) in the visible range (425–680 nm). We systematically investigated seven natural protein crystals (concanavalin, catalase, lysozyme, hemoglobin, α‐chymotrypsin, pepsin, and β‐lactoglobulin) cross‐linked with glutaraldehyde and demonstrated that cross‐linking induces broadband emission that is absent in natural crystals. Focusing on polymorphic lysozyme crystals (tetragonal, orthorhombic, and monoclinic), we found excitation‐dependent fluorescence with lifetimes in the nanosecond range and quantum yields up to 20% (in the monoclinic phase under 450 nm excitation). Single‐ and two‐photon spectroscopy, as well as pressure‐ and solvent‐modulated PL studies, confirm that the emission is due to intermolecular through‐space interactions (TSI) within the crystal lattice. Compression enhances TSI and redshifts the emission, whereas the solvent (DMSO)‐induced swelling reduces TSI and causes a blue shift, establishing a direct structure–emission correlation. This work establishes protein crystals as programmable NLMs with tunable emission and provides a mechanistic framework for the design of nonconventional luminogens through protein crystal engineering.